Pharmacokinetics of ambrisentan in a patient with Pulmonary Arterial Hypertension and a total gastrectomy. (August 2019) - Abston, Eric; Farber, Harrison W.
Abstract: Significant advances have been made in the treatment of arterial pulmonary hypertension (PAH). However, no studies to date have assessed the impact of altered gastrointestinal (GI) anatomy or absorption on the efficacy and bioavailability of oral medications in the treatment of PAH. Here, we describe the treatment of a patient with PAH initially treated with epoprostenol. Subsequently, an intractable upper GI bleed required a total gastrectomy. With epoprostenol, there was near normalization of hemodynamics and she wished to attempt transition to an oral regimen. However, since it was not clear whether oral agents (specifically ambrisentan) would be absorbed and, if so, what the appropriate dose would be, we performed pharmacologic evaluation of ambrisentan absorption in this patient. These investigations identified an effective dose which led to successful transition from epoprostenol.